Hubungan Tingkat Harga Diri dengan Indeks Prestasi Kumulatif Mahasiswa - Lia Khainun Nisa’; Wigyo Susanto; Dwi Heppy Rochmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Self-esteem exerts a significant influence on an individual's confidence and adaptability, indirectly influencing students' academic success. This research seeks to examine the association between self-esteem levels and the Cumulative Grade Point Average (GPA) of students at the Faculty of Economic, Sultan Agung Islamic University, Semarang. This study employs a quantitative approach with a cross-sectional design. The research sample consists of 185 respondents selected randomly using the simple random sampling method. Data were collected through the Rosenberg Self-Esteem Scale (RSES) questionnaire to measure self-esteem levels and students' latest GPA records. Data analysis was conducted using the Spearman correlation test. The findings of this investigation reveal a robust positive correlation between self-esteem levels and students' GPA (p = 0.000; r = 0.774). This suggests that elevated self-esteem is intrinsically linked to improved scholastic performance. This study is anticipated to serve as a foundational reference for support programs aimed at enhancing students' self-confidence. In conclusion, a profound and statistically significant association is evident between self-esteem and students' academic performance.